Literatur Review: Pemetaan Studi Penelitan Tentang Manajemen Keberagamaan, Budaya Organisasi, Kepemimpinan, dan Manajemen Sumber Daya Manusia - Muhammad Rifqi Ramadhan; Daffa Arung Samudra; Rivaldo Berlianto; Lilik Pirmaningsih (Maisyatuna, 2025)
This study aims to map and analyze the development of literature related to diversity management, organizational culture, leadership, and human resource management through a systematic literature review approach. The method used is content analysis of 12 selected scientific journals published between 2017 and 2024. The results of the study indicate that diversity management significantly contributes to improving employee performance, with inclusive leadership, training and development programs, and fair policies as the main supporting factors. Research on organizational culture indicates that organizational values, norms, and customs play an important role in shaping employee loyalty and commitment, although their influence on organizational performance varies depending on the situation and environment. Additionally, it was found that organizational communication factors have a greater influence on performance compared to organizational cultural factors. In terms of leadership, transformational leadership style has been proven to have a positive impact on employee job satisfaction and productivity. Based on this mapping, an integrated framework has been developed that can be used as a reference for further research and strategies for managing workforce diversity, particularly in the context of Indonesia, which has high social and cultural diversity. In general, these findings emphasize the importance of implementing a comprehensive approach to human resource management to achieve organizational effectiveness in a diverse work environment. Keywords: Diversity Management, Organizational Values, Leadership Style, Human Resources, Employee Performance.